Comparing Various Surgical Delay Methods with Ischemic Preconditioning in the Rat TRAM Flap Model - Cinpolat, Ani; Bektas, Gamze; Coskunfirat, Nesil; Rizvanovic, Zumreta; Coskunfirat, O. Koray (Journal of Reconstructive Microsurgery, 2014)
Both surgical delay and ischemic preconditioning (IP) have been shown to be effective in improving the survival of flaps. We used a variety of flap delay methods and IP to increase the surviving area of the transverse rectus abdominis musculocutaneous (TRAM) flap in rats, and the results are compared in between. A 6- × 3-cm–sized TRAM flap in 40 Wistar rats was allocated into five groups. Group 1: TRAM flap was elevated from nondominant pedicle, and the flap was sutured to the original bed. Group 2: Left superior deep epigastric vessels (SDEV) were cut; 1 week later, TRAM flap was elevated. Group 3: Only skin incision was done; 1 week later, TRAM flap was elevated. Group 4: Skin incision was done, and the left SDEV were cut; 1 week later, TRAM flap was elevated. Group 5: TRAM flap was elevated; IP was performed using three cycles of 10 minutes of repeated ischemia/reperfusion (I/R) periods, and the flap was sutured to the original bed. The surviving area of the flap was statistically significant between the control and groups 2, 4, and 5 (p < 0.001), and groups 4 and 2 were superior to group 5. Although preconditioning has been intensively studied for the last two decades and partly provided its beneficial effects in I/R injury, we determined the IP increased the surviving area of the TRAM flap but not effective as much as surgical delay method.
Keywords: ischemic preconditioning; surgical delay; TRAM flap